1997
DOI: 10.1071/p96080
|View full text |Cite
|
Sign up to set email alerts
|

Solid State and Magnetic Properties of Pure, Intercalated and Superconducting Fullerenes

Abstract: A review of some of the solid state and the magnetic properties of fullerenes is presented. We summarise and discuss experimental results on magnetism of pure C60, C70 and higher fullerenes. The main features of the structure and the magnetic properties of intercalated fullerenes, such as metallofullerenes, TDAE-C60 and polymeric A1C60, are presented. Attention is also paid to the mixed state properties of fullerene superconductors, especially to the evaluation of the critical fields and the characteristic len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 138 publications
(197 reference statements)
2
14
0
Order By: Relevance
“…Magnetic measurements carried out with pure C 60 and C 70 fullerene specimens have shown that magnetic transitions are observed at 60 K. 40 This is due to the fact that the currents of p-electrons in the six-and five-membered fullerene rings are different and create a very small but distinct magnetic moment in the fullerene molecule [for C 60 , m = 70.35610 79 A m 2 (see Ref. 27)]. Cooling of specimens of pure C 60 below 90 K results in the transition to ratchet synchronised rotation of the fullerene molecules.…”
Section: Conducting and Magnetic Properties Of Fullerenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic measurements carried out with pure C 60 and C 70 fullerene specimens have shown that magnetic transitions are observed at 60 K. 40 This is due to the fact that the currents of p-electrons in the six-and five-membered fullerene rings are different and create a very small but distinct magnetic moment in the fullerene molecule [for C 60 , m = 70.35610 79 A m 2 (see Ref. 27)]. Cooling of specimens of pure C 60 below 90 K results in the transition to ratchet synchronised rotation of the fullerene molecules.…”
Section: Conducting and Magnetic Properties Of Fullerenesmentioning
confidence: 99%
“…The considerable interest of experts from different areas in fullerenes and compounds based on them is reflected in a number of books and reviews. 19 ± 28 In particular, the reviews are devoted to chemistry, 21 spectroscopy 22 ± 26 and magnetic properties 27 of fullerenes and compounds based on them, as well as to intercalation of fullerenes with alkali and alkaline-earth metals. 13,14,28 The present review generalises for the first time the published data on the synthesis of D ± A compounds based on fullerenes that are formed both through van der Waals interaction and charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high π-electron densities on the round molecules, fullerenes have unique reactivities and properties such as electric conductivity, superconductivity, ferromagnetism, and photoconductivity . Fullerenes act the role of an effective visible-light photosensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes show various interesting properties when they are chemically treated with some electron donors or acceptors; superconductivity, ferromagnetism, and photoconductivity attracted much attention. Among the organic electron donors, tetrakis(dimethylamino)ethylene (TDAE) is one of the strongest donors to form radical ion salts with electron acceptors .…”
Section: Introductionmentioning
confidence: 99%
“…Among the organic electron donors, tetrakis(dimethylamino)ethylene (TDAE) is one of the strongest donors to form radical ion salts with electron acceptors . Mixing C 60 with TDAE easily forms the radical ion salt of C 60 −TDAE, which shows a ferromagnetic transition at low temperature 2a.…”
Section: Introductionmentioning
confidence: 99%